ANALYSIS OF THE ANTIMICROBIAL AND ANTI-BIOFILM ACTIVITY OF NATURAL COMPOUNDS AND THEIR ANALOGUES AGAINST STAPHYLOCOCCUS AUREUS ISOLATES - Mastoor, Sobia; Nazim, Fizza; Rizwan-ul-Hasan, Syed; Ahmed, Khalid; Khan, Shabnam; Nawazish Ali, Syed; Abidi, Syed Hani (Molecules, 2022)
Staphylococcus aureus (S. aureus) is one of the most frequent causes of biofilm-associated infections. With the emergence of antibiotic-resistant, especially methicillinresistant S. aureus (MRSA), there is an urgent need to discover novel inhibitory compounds against this clinically important pathogen. In this study, we evaluated the antimicrobial and anti-biofilm activity of 11 compounds, including phenyl propenes and phenolic aldehydes, eugenol, ferulic acid, sinapic acid, salicylaldehyde, vanillin, cinnamoyl acid, and aldehydes, against drug-resistant S. aureus isolates. (2) Methods: Thirty-two clinical S. aureus isolates were obtained from Alkhidmat Diagnostic Center and Blood Bank, Karachi, Pakistan, and screened for biofilm-forming potential, and susceptibility/resistance against ciprofloxacin, chloramphenicol, ampicillin, amikacin, cephalothin, clindamycin, streptomycin, and gentamicin using the Kirby-Bauer disk diffusion method. Subsequently, 5 representative clinical isolates were selected and used to test the antimicrobial and anti-biofilm potential of 11 compounds using both qualitative and quantitative assays, followed by qPCR analysis to examine the differences in the expression levels of biofilm-forming genes (ica-A, fnb-B, clf-A and cna) in treated (with natural compounds and their derivatives) and untreated isolates. (3) Results: All isolates were found to be multi-drug resistant and dominant biofilm formers. The individual Minimum Inhibitory Concentration (MIC) of natural compounds and their analogues ranged from 0.75–160 mg/mL. Furthermore, the compounds, Salicylaldehyde (SALI), Vanillin (VAN), -methyl-trans-cinnamaldehyde (A-MT), and trans-4-nitrocinnamic acid (T4N) exhibited significant (15–92%) biofilm inhibition/reduction percentage capacity at the concentration of 1–10 mg/mL. Gene expression analysis showed that salicylaldehyde, -methyl-trans-cinnamaldehyde, and -bromotrans- cinnamaldehyde resulted in a significant (p < 0.05) downregulation of the expression of ica-A, clf -A, and fnb-A genes compared to the untreated resistant isolate. (4) Conclusions: The natural compounds and their analogues used in this study exhibited significant antimicrobial and anti-biofilm activity against S. aureus. Biofilms persist as the main concern in clinical settings. These compounds may serve as potential candidate drug molecules against biofilm forming S. aureus.
Keywords: Type of access: Open Access; Staphylococcus aureus; natural compounds; anti-biofilm; antimicrobial; gene expression